The regulatory and protective nature of administrative and procedural legal relations - P. E. Spiridonov (Правоприменение)
The article attempts to analyze administrative and procedural legal relations from the point of view of characterizing the ratio of their regulatory and protective nature.The methodological basis of the article is dialectical, formal-logical methods, formal-legal method and method of interpretation of law.The paper calls into question the possibility of using the protective legal relationship as a basis for distinguishing procedural and material legal relations. The author argues that not all activities and actions that have a protective nature and are carried out in the process of public administration are procedural in nature. The assumption that the emergence of a legal process is connected not only with a protective legal relationship arising from noncompliance with obligations or the occurrence of other situations entailing the use of coercive measures, but also in order to ensure respect for the rights of participants in the process from abuse of power by persons making both interim and final procedural decisions is made. Ensuring the rights of participants in the administrative process is carried out by establishing specific administrative procedural actions, deadlines, administrative procedural decisions, procedural grounds for their adoption, etc. The legal process, including the administrative process, must be considered from the point of view of establishing the truth in the case, but at the same time guarantees must be provided that prevent the abuse of power by on the part of the ruling entity and the right on the part of all participants in the process. At the same time, administrative procedural regulation is aimed not only at establishing legal facts, comprehensiveness, completeness and objectivity of the consideration of an administrative case, but also at protecting the rights of persons involved in the case and ensuring their duties. Hence, the protective nature of administrative and procedural legal relations does not follow from the main substantive legal relationship, but from the corresponding purpose of protecting and ensuring the legitimate procedural rights and obligations of participants in the administrative process.Administrative and procedural legal relations, realizing the regulatory function of law, are formed on the basis of regulatory norms that provide for administrative and procedural rights and obligations of relevant subjects in the consideration and resolution of administrative cases. In addition to the fact that administrative and procedural legal relations are regulatory, they also have a law enforcement character. The regulatory function of administrative and procedural law is expressed in the establishment of not only administrative and procedural actions that should (can) be committed by the subjects of administrative and procedural legal relations when initiating, establishing circumstances, considering an administrative case, but also in their specific sequence, timing of commission, as well as types of administrative and procedural decisions, etc. The protective function of administrative and procedural law is to protect the administrative and procedural rights and interests of all participants in legal relations.Based on the above, the author comes to the conclusion that administrative and procedural legal relations are of a regulatory and protective nature.